Accuracy of Procalcitonin, C-Reactive Protein, and Mean Platelet Volume as Infection Markers in Neonatal Sepsis - Hardiyanti Fitri; Beby Syofiani Hasibuan; Badai Buana Nasution; Arlinda Sari Wahyuni; Ayodhia Pitaloka Pasaribu; Syamsidah Lubis (GLOBAL HEALTH SCIENCE GROUP, 2026)
Neonatal sepsis remains a significant cause of morbidity and mortality, yet diagnosis is limited by nonspecific symptoms and delayed blood culture results. This study evaluated the diagnostic accuracy of procalcitonin (PCT), C-reactive protein (CRP), and mean platelet volume (MPV) as early biomarkers of neonatal sepsis. A retrospective cohort study was conducted in the Neonatology Unit of H. Adam Malik General Hospital, Medan, from January to December 2024. The sampling technique used is consecutive sampling. Of 346 neonates screened, 121 met the inclusion criteria and had concurrent PCT, CRP, MPV, and blood culture results. Clinical and laboratory data were extracted from electronic medical records. Diagnostic performance was assessed using sensitivity, specificity, predictive values, likelihood ratios, and ROC analysis. Among 121 neonates, 31.4% had positive blood cultures. MPV showed no significant difference between culture-positive and culture-negative groups (p = 0.104) and demonstrated limited discriminatory value (AUC 0.592). CRP was significantly associated with culture results (p = 0.037), showing high specificity (94.7%) but low sensitivity (30.0%) at ≥1 mg/L (AUC 0.624). PCT demonstrated the strongest performance, with significantly higher levels in culture-positive neonates (p = 0.022), sensitivity of 64.5%, specificity of 69.0%, and an AUC of 0.672. Diagnostic accuracy was 66.7% for PCT, 85.1% for CRP, and 55.4% for MPV. PCT provided the most balanced diagnostic utility for neonatal sepsis, while CRP served as a highly specific rule-in marker. MPV showed limited usefulness. Although these biomarkers contribute to early assessment, they are insufficient as standalone diagnostic tools and should be integrated with clinical evaluation and microbiological testing.